Biogas Tri-generation for Postharvest Processing of Agricultural Products in a Rural Community: Techno-economic Perspectives. (December 2017) - Lamidi, Rasaq O.; Wang, Yaodong; Pathare, Pankaj B.; Roskilly, A.P.; Aguilar, Marcelo Calispa
Abstract: One third of the global food production ends up in the bins such that food waste now ranks third when placed amongst the world's CO2 emitters. Bulk of food waste occurs at the early stage of food value chain in the developing countries where many people ironically suffer from food insecurity. To reduce this trend, a biogas driven tri-generation system which synchronizes power generation with food drying and cold room storage is designed and analyzed in context of the current renewable energy policy of the Nigerian government. Using Aspen Plus simulator, market wastes from a rural community is analyzed for biogas generation. The biogas is subsequently used to fuel a 72kWe internal combustion engine which drives a generator to generate electricity. The recovered heat from the engine's exhaust is used for drying and cooling of agricultural products while heat from the cooling jacket is used to maintain the anaerobic digestion process. The results from this study show that the system's efficiency increases from 25.66% to 76.02% for electricity only and tri-generation respectively. The results also indicate that the system is able to provide electricity, drying energy requirements and postharvest cold storage for 322, 56, and 922 farming households respectively. This amounts to drying of 20.35MT, 2.313MT and 3.75MT of cassava tubers, maize and tomato respectively per household per year while 3.75MT of tomato is also cold stored. The results equally demonstrate that with the current electricity tariffs for remote areas being charged at USD 13.1/MWh and Feed-in Tariffs (FITs) of USD 122.48/MWh, the Net Present Value is positive regardless of FITs availability and the current banks' lending rates. However, the payback period is sensitive to FITs and lending rates and varies between 2.1years to 7.19 years depending on the lending rates.